Correlations Between Parental Inbred Lines and Derived Hybrid Performance for Grain Filling Traits in Maize - Alvarez Prado, Santiago (2013)
Individual kernel weight (KW) is largely genetically determined, and its variability is achieved through different combinations of rate and duration of kernel growth. Genetic variability for grain-filling patterns has been observed among inbred lines and commercial hybrids, and there is current interest on dissecting its genetic basis. However, suitable grain filling phenotyping protocols are still to be determined, such as the value to study traits at the inbred or hybrid levels. The objective of our study was to evaluate the correlation between parental inbred line and derived hybrid performance for several grain-filling traits in maize (Zea mays L.). We hypothesized that there would be high correlations due to the relative high heritability of grainfilling traits. Three trials were conducted (two in Argentina and one in the United States) with commercial relevant germplasm (totaling 25 parental inbreds and 31 single-cross hybrids). Traits were KW, kernel growth rate (KGR), grainfilling duration (GFD), maximum water content (MWC), moisture concentration at physiological maturity (MCPM), and kernel desiccation rate (KDR) during the effective grain filling. Both heterosis and correlations between midparental value and hybrid performance were significant (p < 0.05) for all traits (r values of 0.63, 0.71, 0.81, 0.83, 0.61, and 0.71 for KW, KGR, GFD, MWC, KDR, and MCPM, respectively). Our results confirm that studying inbred lines for grain-filling traits generates valuable information for derived hybrid performance